2020
DOI: 10.1186/s13018-020-01919-9
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma versus hyaluronic acid in the treatment of knee osteoarthritis: a meta-analysis

Abstract: Background This study aimed to evaluate the clinical efficacy of platelet-rich plasma (PRP) injection compared with hyaluronic acid (HA) injection for patients undergoing knee osteoarthritis. Methods We systematically searched electronic databases including PubMed, Embase, Web of Science, and the Cochrane Library on January 23, 2020 to identify relevant studies issued in English languages. The outcomes evaluating the efficacy of knee osteoarthritis (KOA) treatment were Western Ontario and McMaster Universiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 46 publications
(145 reference statements)
2
49
0
1
Order By: Relevance
“…Therefore, intra-articular injections of PRP might be considered as a disease-modifying effects therapy. Furthermore, a clinical superiority of PRP injections over other intra-articular therapies such as hyaluronic acid has been described 64,65 . Despite the above, the controversy regarding the use of PRP also lies in the results of some well-conducted controlled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, intra-articular injections of PRP might be considered as a disease-modifying effects therapy. Furthermore, a clinical superiority of PRP injections over other intra-articular therapies such as hyaluronic acid has been described 64,65 . Despite the above, the controversy regarding the use of PRP also lies in the results of some well-conducted controlled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In the 20 randomized controlled trials (RCTs) enrolled in their meta-analysis in 2020, it was shown that PRP has a better analgesic effect than HA in long-term recovery (at the 6-month and 12-month follow-ups) and also leads to better functional recovery in 12 months. The risk of adverse events was not increased compared with HA [ 95 ]. Similar observations were noted by Trams et al in their meta-analysis [ 96 ].…”
Section: Platelets As a Treatment For Oamentioning
confidence: 99%
“…Two meta-analyses, of 12 and 10 studies, respectively, comparing the effects of PRP and HA, found that patients in the PRP group showed a statistically significant difference in pain reduction (measured by VAS and WOMAC pain scales) at 6 and 12 months’ follow-up, while there was no observed difference for clinical outcomes measured by KOOS and other WOMAC scales [ 76 , 81 ]. Meta-analyses, including 20 and 15 studies respectively, comparing PRP to HA by Tang et al and Han et al demonstrated a positive effect for both pain and function scores, and a meta-analysis by Zhang et al reported an improvement in the WOMAC function score at 12 months’ follow-up, while there was no significant difference between methods at 6 months after the treatment [ 82 , 83 , 84 ]. A meta-analysis by Chen et al found that WOMAC total scores superiorly improved in patients treated with PRP compared with patients treated with HA [ 85 ].…”
Section: Intra-articular Injectionsmentioning
confidence: 99%